Association of Genetic Variants rs1888747 and rs10868025 of FRMD3 Gene with Diabetic Nephropathy in Pakistani Patients - Farkhanda Sharif, Mah Noor Hassan, Haris Abdul Rehman, Rida Malik, Syeda Safina, Ayesha Ameen, Syeda Anamta Hashmi, Sumaira Hanif, Aqsa Qurban, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Diabetic Nephropathy is also known as diabetic kidney disease. The major cause of diabetic nephropathy is diabetes Many candidate genes and genome-wide association studies have proved that gene FRMD3 is highly associated with diabetic nephropathy. Aim of the study: This study aimed to investigate the association of rs1888746 and rs1888747 with diabetic nephropathy in our local population of Pakistan. Research Design: For this study, we enrolled 50 physician-diagnosed patients and 25 healthy control from the young population. Genomic DNA was extracted by organic method and visualized on Agarose gel. Methodology: Monoplex PCR, real-time PCR, genotyping via high-resolution melting curve analysis,and SPSS software were used to accomplish the research work. Results: Our study found that variant rs1888746 shows an insignificant association with (p<0.0982) and rs188747 shows a significant association with (p<0.0498), but results need to be confirmed on a larger scale. Conclusion: The results concluded that our selected rs1888747 on FRMD3 gene shows the allelic association with diabetic nephropathy in Pakistani local population whereas r1888746 did not. Keywords: Genome Wide Association Studies, Diabetic Nephropathy, Genomic DNA, FRMD3 gene